REAKSI PASAR TERHADAP PENGUMUMAN KENAIKAN DAN PENURUNAN DIVIDEN PADA INDUSTRI PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2010 - Siti Nur Aisah; Tina Sulistiyani (Universitas Ahmad Dahlan, 2012)
This study aims to determine how the market reaction to announcements of dividend increases and decreases in the Banking Companies listed on the Indonesia Stock Exchange 2008-2010 period. This study population was 31 banking companies that announced dividend increases and decreases during the period 2008-2010. Data collection technique used was purposive sampling. Of the 31 existing populations, selected 7 samples that meet the criteria penelitian. Teknik analysis of the data used is the one sample t-test. The research proves that in 2009 the abnormal return only occurs on day 5 before the announcement of devidend increase, while the other day, thus indicating no abnormal return. Research in 2010, it is known that there is no abnormal return on announcement of an increase or descrease in dividends.